MODERASI TAREKAT PERSPEKTIF SYEKH H. ALI IMRAN HASAN - Nofri Andy N; Mufti Ulil Amri (Turast: Jurnal Penelitian dan Pengabdian, 2020)
This article discusses the views of Sheikh H. Ali Imran Hasan regarding tarekat moderation. This paper departs from the development of the tarekat and the attitude of exclusivity in charity, which is often a moderation process in the tarekat. According to Sheikh H. Ali Imran Hasan, knowledge and charity are two important aspects in studying the tarekat as well as monitoring the development of the tarekat. The method used in this research is descriptive qualitative. The conclusions of this study include: (1) the importance of a complete and comprehensive understanding in studying the tarekat (2) a rational and open attitude can eliminate boredom in thinking for students (3) the need to pay attention to public acceptance of the tarekat to avoid